Abiotic and Biotic Stress in Plants 2019
DOI: 10.5772/intechopen.84565
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Cuticular Wax, a Trait for Multiple Stress Resistance in Crop Plants

Abstract: Cuticular waxes form the primary interface between a plant and its external environment. The most important function of this hydrophobic interface is regulation of non-stomatal water loss, gas exchange and conferring resistance to a wide range of biotic as well as abiotic stresses. The biosynthesis, transport and deposition of the cuticular waxes are tightly coordinated by complex molecular networks, which are also often regulated in response to various developmental, biotic as well as abiotic cues. Evidences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 171 publications
(123 reference statements)
1
15
0
Order By: Relevance
“…ABCG were also considered to be essential components of the plant immune system [ 86 ]. This is consistent with the observation that epicuticular waxes play roles in plant-insect interactions [ 87 , 88 ]. This aspect makes our putative gene an interesting research object in the context of rye resistance to pathogens.…”
Section: Discussionsupporting
confidence: 92%
“…ABCG were also considered to be essential components of the plant immune system [ 86 ]. This is consistent with the observation that epicuticular waxes play roles in plant-insect interactions [ 87 , 88 ]. This aspect makes our putative gene an interesting research object in the context of rye resistance to pathogens.…”
Section: Discussionsupporting
confidence: 92%
“…A key innovation in the plant evolutionary history was the development of the cuticle with its cuticular waxes, the first line of physical barrier against any external factors [1][2][3]. Several studies have shown cuticular waxes play an important role in the plant's response to abiotic and biotic stresses [1,2,4,5]. Most importantly, its role in protection against nonstomatal water loss has been described extensively in both monocot and dicot plant species [2].…”
Section: Introductionmentioning
confidence: 99%
“…We observed a significant RTx430-specific 34-fold increase in 3-ketoacyl-CoA synthase (UniProt identifier A0A1B6PJK5), which catalyzes the first step in very-long-chain fatty acids (VLCFAs) necessary for epicuticular wax production [ 47 ]. Epicuticular wax is important for drought tolerance in multiple species [ 48 ], and its abundance in grass crops correlated with grain yield under drought stress [ 49 ], including sorghum [ 50 , 51 ]. Multiple drought-relevant proteins became significantly less abundant exclusively in organelle-enriched RTx430 during water deficit.…”
Section: Resultsmentioning
confidence: 99%